The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/molecules27206945
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration, Characterization and Thermal Decomposition Kinetics of New Nanoenergetic Composite Based on Hydrazine 3-Nitro-1,2,4-triazol-5-one and Nanostructured Cellulose Nitrate

Abstract: This research aims to develop new high-energy dense ordinary- and nano-energetic composites based on hydrazine 3-nitro-1,2,4-triazol-5-one (HNTO) and nitrated cellulose and nanostructured nitrocellulose (NC and NMCC). The elaborated energetic formulations (HNTO/NC and HNTO/NMCC) were fully characterized in terms of their chemical compatibility, morphology, thermal stability, and energetic performance. The experimental findings implied that the designed HNTO/NC and HNTO/NMCC formulations have good compatibiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The first decomposition peak for both energetic composites is related to the thermolysis of nitrate ester binders, where the main produced species, identified using TG-FTIR, were found to be NxOy/CO 2 [42], whereas the other exothermic events are attributed to the high and low decomposition stages of HNTO salt [19]. Additionally, it is obvious from Table 1 and Figure 4 [43], supporting the TGA/DTG results. Another interesting result is that the ∆H T of NNC/HNTO/MgAl-CuO (e.g., 1520 J•g −1 at 15 • C/min) is higher than that of NC/HNTO/MgAl-CuO (e.g., 793.6 J•g −1 at 15 • C/mn), confirming once more the effectiveness of switching from NC to its nanostructured derivative as well as the role of MgAl-CuO nanothermite as a high-energy-density material that would increase heat production [44].…”
Section: Samplesupporting
confidence: 73%
See 1 more Smart Citation
“…The first decomposition peak for both energetic composites is related to the thermolysis of nitrate ester binders, where the main produced species, identified using TG-FTIR, were found to be NxOy/CO 2 [42], whereas the other exothermic events are attributed to the high and low decomposition stages of HNTO salt [19]. Additionally, it is obvious from Table 1 and Figure 4 [43], supporting the TGA/DTG results. Another interesting result is that the ∆H T of NNC/HNTO/MgAl-CuO (e.g., 1520 J•g −1 at 15 • C/min) is higher than that of NC/HNTO/MgAl-CuO (e.g., 793.6 J•g −1 at 15 • C/mn), confirming once more the effectiveness of switching from NC to its nanostructured derivative as well as the role of MgAl-CuO nanothermite as a high-energy-density material that would increase heat production [44].…”
Section: Samplesupporting
confidence: 73%
“…According to Figures 5 and 6, there is an increase in Ea and log(A) as a function of conversion in the first and second stages of decomposition for both energetic composites. Meanwhile, it is important to note that the mean Ea values obtained for the first thermolysis process, related to the thermolytic splitting of O-NO 2 groups of NNC/HNTO/MgAl-CuO composite (~104 kJ/mol), are lower than those of the NC/HNTO/MgAl-CuO composite (~139 kJ/mol), which are even lower than those of the NC/HNTO (~139 kJ/mol) and NNC/HNTO (~119 kJ/mol) baselines, as well as NC (~172 kJ/mol) and NNC (~156 kJ/mol) binders [43,52]. These findings indicate that MgAl-CuO nanothermite is a key factor in accelerating the thermolysis of nitrated cellulose chains through the physical adsorption of the nitrous oxides in the active sites of the nanothermite solid surface, which will inhibit their diffusion to the outer atmosphere, therefore, keeping the NO 2 molecules stagnant within the NC-based formulation and, hence, increasing the autocatalytic thermal decomposition of the NC/HNTO and NNC/HNTO composites [41].…”
Section: Determination Of the Decomposition Kinetic Parametersmentioning
confidence: 82%
“…The energetic properties of CNs are in demand as constituents of explosive compositions [ 8 , 9 , 10 , 11 ] in the mining industry, road construction in mountainous areas, and focused demolition of obsolete structures because the safety and handling issues associated with CN-based compositions have currently been resolved at a very high level [ 12 ]. It should be emphasized that CNs themselves have become precursors of more complex chemicals with unique energetic characteristics [ 13 ]. An overview of the published data on the demand for CNs in the industry allows for the conclusion that there is an increasing need for CNs with a nitrogen content ranging from 10.6% to 12.0%.…”
Section: Introductionmentioning
confidence: 99%
“…Kokuryo et al (2022) [ 20 ] studied the catalytic degradation of LDPE using two types of catalysts (zeolite β and zeolite MTES-β) at 5 K/min heating rate. They concluded that zeolite MTES-β pushed LDPE to decompose at a lower temperature than zeolite β. Dourari et al (2022) [ 21 ] and Tarchoun et al (2022) [ 22 ] developed new composites with different materials and tested them using various analytical techniques. They concluded that there was a big drop in the activation energy of the thermal behavior.…”
Section: Introductionmentioning
confidence: 99%